2004
DOI: 10.1016/j.neuro.2003.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Maltolate-Induced Toxicity in NT2 Cells Occurs Through Apoptosis and Includes Cytochrome c Release

Abstract: Aluminum (Al) compounds are neurotoxic and have been shown to induce experimental neurodegeneration although the mechanism of this effect is unclear. In order to study this neurotoxic effect of Al, we have developed an in vitro model system using Al maltolate and human NT2 cells. Al maltolate at 500 mM caused significant cell death with a 24-h incubation and this toxicity was even more evident after 48 h. Lower doses of Al maltolate were also effective, but required a longer incubation for cell death. Nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 51 publications
0
15
1
Order By: Relevance
“…The current result revealed that AlCl 3 administration produced significant (P < 0.05) increase in brain caspase-3 (26.92%) and P53 (47.33%) levels with significant decrease (P < 0.05) in brain BCL2 level (À49.36%) when compared with the negative control group. A strong body of evidence indicated the potential role of Al in inducing apoptosis and neurodegeneration in the brain in vivo [52] as well as in vitro [53].…”
Section: Effect Of Tested Compounds Administration On Brain Caspase-3mentioning
confidence: 99%
“…The current result revealed that AlCl 3 administration produced significant (P < 0.05) increase in brain caspase-3 (26.92%) and P53 (47.33%) levels with significant decrease (P < 0.05) in brain BCL2 level (À49.36%) when compared with the negative control group. A strong body of evidence indicated the potential role of Al in inducing apoptosis and neurodegeneration in the brain in vivo [52] as well as in vitro [53].…”
Section: Effect Of Tested Compounds Administration On Brain Caspase-3mentioning
confidence: 99%
“…3,4) In fact, some evidence supports the selective accumulation of Al within neurons containing neurofibrillay tangles in patients with Alzheimer's disease and within the aging human brain. 1,5) Meiri et al, have also reported that brain Al concentrations reach submilimolar levels in some encephalopathies.6) Several lines of research that use cultured cells and the aluminum-maltolate complex (Al(maltol) 3 ), which is a membrane permeable, lipophilic complex of Al, also showed that the exposure of cells such as the Neuro-2a murine neuroblastoma cells, 7) human NT2 neuroblastoma cells, 8) and PC12 cells 9,10) to the Al complex results in a decrease in cell viability via the apoptotic cell death pathway. Recently, we have reported that the treatment of PC12 cells with Al(maltol) 3 causes a decrease in the levels of the intracellular reduced glutathione depending on the amount of Al(maltol) 3 accumulated in the cells.…”
mentioning
confidence: 99%
“…6) Several lines of research that use cultured cells and the aluminum-maltolate complex (Al(maltol) 3 ), which is a membrane permeable, lipophilic complex of Al, also showed that the exposure of cells such as the Neuro-2a murine neuroblastoma cells, 7) human NT2 neuroblastoma cells, 8) and PC12 cells 9,10) to the Al complex results in a decrease in cell viability via the apoptotic cell death pathway. Recently, we have reported that the treatment of PC12 cells with Al(maltol) 3 causes a decrease in the levels of the intracellular reduced glutathione depending on the amount of Al(maltol) 3 accumulated in the cells.…”
mentioning
confidence: 99%
“…Aluminium (Al) compounds are neurotoxic and have been shown to induce experimental neurodegeneration although the mechanism of this effect is unclear [3,8]. Aluminium has the ability to promote formation and accumulation of insoluble beta amyloid (A beta) and hyperphosphorylated tau [27,28].…”
Section: Introductionmentioning
confidence: 99%